Alcohol induces neural tube defects by reducing retinoic acid signaling and promoting neural plate expansion - Edri, Tamir; Cohen, Dor; Shabtai, Yehuda; Fainsod, Abraham (Frontiers in Cell and Developmental Biology, 2023)
Neural tube defects (NTDs) are among the most debilitating and common developmental defects in humans. The formation of NTDs has been attributed to abnormal folic acid (vitamin B9) metabolism, excess retinoic acid (RA) signaling, diet, environmental factors, and others. In the present study, we show that reducing RA signaling levels using retinaldehyde dehydrogenase inhibitors (ethanol, DEAB, and citral) or Cyp26a1-driven degradation efficiently induce NTDs. These NTDs can then be rescued by providing exogenous vitamin A, the precursor of RA, or other retinoids, thus supporting the involvement of reduced RA signaling in their formation and further reinforcing the fact that RA signaling is required for normal neural tube closure during embryogenesis. We mapped this RA requirement to early gastrula stages where it is required for the neural precursor formation process. Reduced RA signaling results in increased proliferation of neural precursors resulting in an expanded neural plate, driven by abnormal expression of neural network genes, including the neural plate stem cell maintenance genes, geminin, and foxd4l1.1. These results show that RA signaling plays a very early role in the proliferation and differentiation of the neural plate and its disruption leads to the formation of NTDs.